The central role of mindful parenting in child’s emotional regulation and human flourishing: a blueprint perspective - Sansone, Antonella (Frontiers in Psychology, 2024)
This article provides an innovative perspective of emotional-regulation and human flourishing which acknowledges the fundamental role of early parent-child experiences in shaping brain structure and functioning involved in emotional regulation and the central role of mindful parenting in facilitating emotional regulation in both parent and child (co-regulation).In this perspective paper the author underlines not only the central role of emotions and emotional regulation in human development and flourishing, but also the importance of maternal mental health, mindfulness, and a connected supportive community during pregnancy and postnatally in facilitating emotional regulation in both the caregiver and the infant and thus promoting secure attachment. The role of alloparenting and how we evolved to share childrearing is introduced, and emotional regulation is described not as an individual phenomenon but a relational embodied process. The associations between right brain functioning, mindfulness and secure attachment, all leading to emotional regulation, wellbeing, and resilience are described. Sharing findings and perspectives offer an opportunity for insights and reflection upon what strategies could be created to promote relational emotional regulation and wellbeing in early life, thus human flourishing leading to a peaceful society.